Incidence of saprolegniasis in fishes of Hataikheda reservoir, Bhopal - Salgotra, Vikas; Mastan, S A; Qureshi, T A (Indian Journal of Fisheries, 2011)
A total of 12 isolates of fungi were obtained from diseased fishes which belongsto four species namely Saprolegnia parasitica, Saprolegnia ferax,Saprolegnia hypogyana, Saprolegnia diclina. All these fungi were isolated fromfour different species of fishes viz. Channa gachua, Channa straitus, Channapunctatus, Clarias batrachus. The parasitic ability of all the twelve fungi wasconfirmed by conducting pathogenicity tests under laboratory conditions usinghealthy fishes of the same species. All the species of fungi were found to bepathogenic to fish. But Saprolegnia parasitica was more virulent showing infectionwithin eight hours.